Tìm x:
a)x+3/4=5/3
b)x-2/3=7/2
Tìm x:
a)x(x+4)+(5+x)(5-x)=3
b)(2x-3)^2=(4x+3)^2
mình cảm ơn
\(a,\Rightarrow x^2+4x+25-x^2=3\\ \Rightarrow4x=-22\Rightarrow x=-\dfrac{11}{2}\\ b,\Rightarrow\left(2x-3-4x-3\right)\left(2x-3+4x+3\right)=0\\ \Rightarrow6x\left(-2x-6\right)=0\Rightarrow\left[{}\begin{matrix}x=-3\\x=0\end{matrix}\right.\)
tìm x:
a)3(2x-3)+2(2-x)=-3
b)2x(x2-2)+x2(1-2x)-x2=-12
c)3x(2x+3)-(2x+5)(3x-2)=8
d)4x(x - 1) - 3(x2-5)-x2=(x-3)-(x+4)
e)2(3x-1)(2x+5)-6(2x-1)(x+2)=-6
a: Ta có: \(3\left(2x-3\right)+2\left(2-x\right)=-3\)
\(\Leftrightarrow6x-9+4-2x=-3\)
\(\Leftrightarrow4x=2\)
hay \(x=\dfrac{1}{2}\)
Tìm x:
a) 2/5 = 3/4 : x = -1/2
b) 5/7 - 2/3 . x = 4/5
c) 1/2x + 3/5x = -2/3
d) 4/7x - x = -9/14
b: \(\dfrac{5}{7}-\dfrac{2}{3}\cdot x=\dfrac{4}{5}\)
=>\(\dfrac{2}{3}x=\dfrac{5}{7}-\dfrac{4}{5}=\dfrac{25-28}{35}=\dfrac{-3}{35}\)
=>\(x=-\dfrac{3}{35}:\dfrac{2}{3}=\dfrac{-3}{35}\cdot\dfrac{3}{2}=-\dfrac{9}{70}\)
c: \(\dfrac{1}{2}x+\dfrac{3}{5}x=-\dfrac{2}{3}\)
=>\(x\left(\dfrac{1}{2}+\dfrac{3}{5}\right)=-\dfrac{2}{3}\)
=>\(x\cdot\dfrac{5+6}{10}=\dfrac{-2}{3}\)
=>\(x\cdot\dfrac{11}{10}=-\dfrac{2}{3}\)
=>\(x=-\dfrac{2}{3}:\dfrac{11}{10}=-\dfrac{2}{3}\cdot\dfrac{10}{11}=\dfrac{-20}{33}\)
d: \(\dfrac{4}{7}\cdot x-x=-\dfrac{9}{14}\)
=>\(\dfrac{-3}{7}\cdot x=\dfrac{-9}{14}\)
=>\(\dfrac{3}{7}\cdot x=\dfrac{9}{14}\)
=>\(x=\dfrac{9}{14}:\dfrac{3}{7}=\dfrac{9}{14}\cdot\dfrac{7}{3}=\dfrac{3}{2}\)
Tìm x:
a) x - \(\dfrac{5}{7}\) = \(\dfrac{3}{5}\) x \(\dfrac{1}{2}\) b) x \(x\dfrac{2}{3}=\dfrac{5}{8}+\dfrac{3}{4}\)
\(a,x-\dfrac{5}{7}=\dfrac{3}{5}\times\dfrac{1}{2}\)
\(x-\dfrac{5}{7}=\dfrac{3}{10}\)
\(x=\dfrac{3}{10}+\dfrac{5}{7}\)
\(x=\dfrac{21}{70}+\dfrac{50}{70}\)
\(x=\dfrac{71}{70}\)
\(Vayx=\dfrac{71}{70}\)
\(b,x\times\dfrac{2}{3}=\dfrac{5}{8}+\dfrac{3}{4}\)
\(x\times\dfrac{2}{3}=\dfrac{5}{8}+\dfrac{6}{8}\)
\(x\times\dfrac{2}{3}=\dfrac{11}{8}\)
\(x=\dfrac{11}{8}:\dfrac{2}{3}\)
\(x=\dfrac{11}{8}\times\dfrac{3}{2}\)
\(x=\dfrac{33}{16}\)
\(Vayx=\dfrac{33}{16}\)
2. Tìm x:
a) 4/5 + x = 2/3
b) 1/2 - x = 7/12
c) 3 và 1/2 : x = -7/2
d) 3/8 - 1/6 x =5/2
e) x + 50%x = -1,5
a: x=2/3-4/5=10/15-12/15=-2/15
b: 1/2-x=7/12
=>x=1/2-7/12=-1/12
c: =>7/2:x=-7/2
=>x=-1
d: =>1/6x=3/8-5/2=3/8-20/8=-17/8
=>x=-17/8*6=-102/8=-51/4
e: =>1,5x=-1,5
=>x=-1
Tìm x:
a) 4.(2-x)+x.(x+6)=x2
b) x.(x-7)-(x-2).(x+5)=0
c) (2x+3).(3-2x)+(2x-1)2=2
a: Ta có: \(4\left(2-x\right)+x\left(x+6\right)=x^2\)
\(\Leftrightarrow8-4x+x^2+6x-x^2=0\)
\(\Leftrightarrow2x=-8\)
hay x=-4
b: Ta có: \(x\left(x-7\right)-\left(x-2\right)\left(x+5\right)=0\)
\(\Leftrightarrow x^2-7x-x^2-3x+10=0\)
\(\Leftrightarrow-10x=-10\)
hay x=1
c: Ta có: \(\left(2x+3\right)\left(3-2x\right)+\left(2x-1\right)^2=2\)
\(\Leftrightarrow9-4x^2+4x^2-4x+1=2\)
\(\Leftrightarrow-4x=-8\)
hay x=2
Tìm x:
a) 2x - 2/3 = -3/4
b) x : 3/4 + 1/4 = -2/3
c) 1/4x + 2/5 = 7/5
d) /x//5 - 2 = -3/5
MÌNH CẦN GẤP. CẢM ƠN Ạ
`c)1/4x+2/5=7/5`
`=>1/4x=7/5-1/5=1`
`=>x=1:1/4=4`
Vậy `x=4`
`a)2x-2/3=-3/4`
`=>2x=-3/4+2/3=-1/12`
`=>x=-1/24`
Vậy `x=-1/24`
`b)x:3/4+1/4=-2/3`
`=>x:3/4=-2/3-1/4=-11/4`
`=>x=-11/4 xx 3/4=-33/16`
Vậy `x=-33/16`
Tìm x:
a) √x = 3
b) √x = 6
c) √x = 8
d) √x = 12
e) 2√x = 10
f) 3√x = 21
g) √x = 8
h) 2 + √x = 11
\(a,\sqrt{x}=3\Leftrightarrow x=9\\ b,\sqrt{x}=6\Leftrightarrow x=36\\ c,\sqrt{x}=8\Leftrightarrow x=64\\ d,\sqrt{x}=12\Leftrightarrow x=144\\ e,2\sqrt{x}=10\Leftrightarrow\sqrt{x}=5\Leftrightarrow x=25\\ f,3\sqrt{x}=21\Leftrightarrow\sqrt{x}=7\Leftrightarrow x=49\\ g,\sqrt{x}=8\Leftrightarrow x=64\\ h,2+\sqrt{x}=11\Leftrightarrow\sqrt{x}=9\Leftrightarrow x=81\)
a. \(\sqrt{x}=3\)
<=> \(\left(\sqrt{\sqrt{x}}\right)^2-\left(\sqrt{3}\right)^2=0\)
<=> \(\left(\sqrt{\sqrt{x}}-\sqrt{3}\right)\left(\sqrt{\sqrt{x}}+\sqrt{3}\right)=0\)
<=> \(\left[{}\begin{matrix}\sqrt{\sqrt{x}}-\sqrt{3}=0\\\sqrt{\sqrt{x}}+\sqrt{3}=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=9\\x=\left(Vnghiêm\right)\end{matrix}\right.\)
Vậy nghiệm của PT là S = \(\left\{9\right\}\)
a) \(\sqrt{x}=3\Leftrightarrow x=9\)
b) \(\sqrt{x}=6\Leftrightarrow x=36\)
c) \(\sqrt{x}=8\Leftrightarrow x=64\)
d) \(\sqrt{x}=12\Leftrightarrow x=144\)
e) \(2\sqrt{x}=10\Leftrightarrow\sqrt{x}=5\Leftrightarrow x=25\)
f) \(3\sqrt{x}=21\Leftrightarrow\sqrt{x}=7\Leftrightarrow x=49\)
g) \(\sqrt{x}=8\Leftrightarrow x=64\)
h) \(2+\sqrt{x}=11\Leftrightarrow\sqrt{x}=9\Leftrightarrow x=81\)
Tìm x:a) x - 2 + 7 = 1 . 3 . -9
b) 4 . x - 1 = (-5) 5 12 2 4 16 9 2 9
c) -2 . x + 5 = 7
d) 2 . x : 7 . 1 = 29 3 8 12 5 3 8 15